الفرقة الاسلامية اسباب نشائها و صفاتها و اثرها - Syarif Zubaidah (Millah: Journal of Religious Studies, 2008)
The emergence of religious sects has caused fidgetiness among society, whether in a religious community itself or in social interaction in general. Historically, the emergence of religious sects takes place across times and centuries. It emerged by the time the religion was born. In Islam history for example, it has been widely known the genesis of sect khawarij and syiah in the phase of shahabah (companion of Prophet Muhammad) . Recently, in Indonesia especially, have emerged some sects considered as deviate, such as Jamaah Ahmadiyah, Al-Qiyâdah Al-Islâmiyyah, Quran Suci, etc. This has caused strained situation among society. In many of regions, people massively protested the existence of the sects. Often, it followed by damaging the properties of the sects, such as houses and masjid. This article described definition and characteristics of religious sects, whether it is good or deviate. This article also elucidated the causal factors of the emergence of those sects and also its impacts toward society’s life. The study showed that: the right sects are those who persistently hold the norms and values of Al-Qur’an, Sunnah, and follow the behavior of shahabah. While the causal factors of the religious sects emergence are: economic factor, political factor, and the divergence of way of thinking. The impact of the emergence of those various religious sects are: aqidah divergence, political movement divergences, and adhering strictly to the sect and ignoring strictly to the others. This is for example: Mu’tazilah differs fundamentally from Ahlussunnah wal jamaah, Khawarij differs from Syiah, Qadariyah differs from Jabariyah. Each sect claimed that their opinion is the most truthful and the other is wrong/ astray.